FRAMING ANALYSIS NEWS COMPARISON OF BOMB SAMARINDA IN KOMPAS.COM AND TEMPO.CO - Zulfayani "; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The country of Indonesia insisted in the storm with the action of the bombing. At the end of 2016 yesterday, Indonesia was again shaken by the emergence of a Molotov cocktail action that took place in front of the East Kalimantan Samarinda Oikumene Church. The bomb blast occurred on November 13, 2016. The bombing event that injured 4 children, one of whom died from burns in the suffering reached 78%. The bomb incident did not escape the media spotlight, not least the online media. Similarly, kompas.com and tempo.co always preach this case in a series every day.This research is a qualitative research with approach of framing analysis model of Zhongdang Pan and Gerald M. Koscki by using constructionist theory. The object of research in this study are news related to the case of Samarinda bombs at kompas.com and Tempo.co taken in a series each day based on different topics from November 13, 2016 - November 20, 2016.Based on the results of this study, it appears that the attitude kompas.com more positive image of the police, this can be seen from the news raised as telling about the success of the police arrested the suspected Church bombing in Samarinda, then the success of the police captured the brains of Samarinda bombers, Then found evidence in the form of an ISIS flag stating that the perpetrator is connected with ISIS. Tempo.co reporters also highlight the positive image of the police, ranging from the arrest of the main perpetrators of Samarinda bombs, investigations, to the establishment of 7 suspects but on the other hand tempo.co provide opportunities for readers to convey criticism. This is evident from one of the news that tempo.co preached to include criticism from the reader of Tuesday 15 November 2016 edition.Jom FISIP Volume 4 No.2 Oktober 2017 Page 2Keywords: framing analysis, Samarinda bombing news, kompas.com and tempo.co